Peace Education and the Promotion of Peace-building Initiatives through Health Care Programs in Conflict-Affected Areas in Mindanao - Baquial, Elvira (JPAIR Multidisciplinary Research, 2020)
For several years now, there has been a growing global consciousness on the close connection between health and peace. This study aimed to describe peace education and determine the promotion of peace-building initiatives through healthcare programs in conflict-affected areas in Mindanao. The study utilized the descriptive research design and correlation method using survey, interview, and Focus Group Discussion, to 250 survey respondents, eight informants, and 16 FGD participants from conflict-affected areas of Maguindanao and North Cotabato. Data were analyzed and interpreted using mean and multiple regression methods. The study found out that the delivery of the health care programs, the performance of the roles and responsibilities of the healthcare providers, and the use of peace mechanisms were moderately extensive. That peace education has significantly contributed to the promotion of peace-building initiatives in conflict-affected areas. However, the health care programs and health to peace mechanisms strongly influence peace education. The study concludes that health care programs have been delivered well, although there is still a need for improvement in terms of the performance of the roles and responsibilities of the health care providers. The use of peace mechanisms still needs to be intensified.